Indoor nature exposure and influence on physiological stress markers. Issue 6 (18th August 2021) - McSweeney, Jill; Johnson, Shannon; Sherry, Simon; Singleton, Jerome; Rainham, Daniel
ABSTRACT: Spending time in nature is beneficial for stress reduction and recovery. Using the properties of biophilic design, this study examined the influence of a nature-based indoor environment on physiological stress systems. An experimental study was designed to assess the influence of indoor natural elements on autonomic activity (heart rate variability or HRV), self-reported environmental assessments. No differences in heart rate variability were found between participants assigned to either condition. The room with natural elements was rated more positively than the room without natural elements. Participant preference had more impact on changes in HRV for participants without exposure to natural elements. The results suggest that natural elements in indoor environments may influence the regulation of stress response via environmental preference. Abbreviations : ANCOVA: Analysis of Covariance; ANS: Autonomic Nervous System; AVNN: Average of NN; DST: Digit Span Test; EAS: Environmental Assessment Scale; ECG: Electrocardiograph; fMRI: Functional magnetic resonance imaging; HF: High Frequency; HRV: Heart Rate Variability; INE: Indoor Nature Exposure; NR: Nature-Relatedness Scale; PANAS: Positive and Negative Affect Schedule; SAM: Search and Memory Test; SLSI: Student Life Stress Inventory; SMT: Sentence Making Test